Study of Biochemical Parameters among Hospital Admitted Dengue Patients from Day of Admission to Discharge: A Cross Sectional Study (London Journal of Medical and Health Research, 2025)
Background: Dengue fever is an alarming viral public health issue in a large endemic population in the tropical and sub-tropical areas of the world. Recently it has been reported that about 50 million dengue infections occur annually and approximately 2.5 billion people live in dengue endemic countries. As epidemiological factors and presentations of dengue fever varies; hence, laboratory diagnosis and analysis is extremely essential.Objective: This study aims to analyze the biochemical parameters in adult patients diagnosed with dengue at a tertiary care hospital on their day of admission and discharge. Materials and Methods: A cross-sectional laboratory-based study was conducted in Green Life Hospital in Dhaka from June 2023 to December 2023. About 126 seropositive (Dengue NS1 Antigen and IgG and IgM Antibodies) patients were included in the study. After taking informed written consent, blood samples were collected from the subjects for biochemical tests that include serum albumin, AST,ALT, creatinine, urea and electrolyte profile. Data were cleaned, entered and analyzed by Statistical Package for the Social Sciences (SPSS) software version 26.0.Results: Serum albumin, ALT, AST, creatinine , sodium level and urea were found to be elevated among dengue patients on day of admission and all became normal on day of discharge. This study also found that serum albumin was negatively correlated with serum ALT and creatinine on both admission and discharge days.Conclusion: Since dengue does not have specific medical therapy, awareness of altered biochemical parameters will facilitate the clinician in prompt yet appropriate management leading to a good prognosis of the disease.
Keywords: urogenital abnormality; anorectal malformation; Creatinine; Electrolytes; Urea.; Biochemical parameters; dengue patients; serum albumin; serum ALT